Penguatan Akreditasi Laboratorium Kesehatan Daerah dinas Kesehatan Kabupaten Indragiri hilir: Strengthening Accreditation of Regional Health Laboratories, Indragiri hilir District Health Service - Willy Anthony Iqnatius; alif rahman habibi (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
In order to improve health development, the Central Government and Regional Governments must be able to provide equitable, affordable and quality health services. The Health Laboratory is an important part of a health system in providing health services to the community. Health laboratory as an integral part of health services in health facilities. delivery of material The team delivered material on strengthening regional health laboratory accreditation (labkesda) at the Indragiri downstream district health office. This material includes the definition of accreditation of health laboratories, steps in strengthening accreditation, to ensure quality improvement, performance improvement and risk management implementation. From the activities that have been carried out, it can be concluded that participants understand the importance of strengthening health laboratory accreditation because it can provide a sense of security to patients during examinations considering that the laboratories used are standardized